The Influence of the BI-7 Day Reverse Repo Rate (BI7DRR), Money Supply (M2), and Public Savings on Inflation in Indonesia for the Period 2016:Q1-2023:Q4 - Koraag, Putri; Maramis, Mauna; Niode, Audie (PT FORMOSA CENDEKIA GLOBAL, 2024)
Inflation is an economic condition in which the costs of things and services keep going up. Most of the time, a moderate amount of inflation is good for an economy. However, high or unstable inflation can make the economy less stable. The goal of this study is to find out how the Money Supply (M2), Public Savings, and the BI-7 Day Reverse Repo Rate all affect inflation in Indonesia at different times and in different ways. The method used for this work is multiple linear regression analysis. The study's results show that community funds have a strong and negative effect on inflation, the money supply (M2) has a strong and positive effect on inflation, and the BI-7 Day Reverse Repo Rate has a partly negative and significant effect on inflation. Then, the BI-7 Day Reverse Repo Rate, the Money Supply (M2), and Public Savings all have a big effect on inflation at the same time.